Timber Testing in India - Limaye, V. D. (Indian Forester, 1939)
Anogeissus pendula (kardhai) from the United Provinces is found to be the toughest timber so far tested at the Forest Research Institute, Dehra Dun, and, as far as we know, it has withstood a greater blow from a nity pounds hammer than any other timber so far tested in any other laboratory in the world. Although it is a small tree, a considerable Octoberly output is available. The timber is, at present, used only for firewood and charcoal but it deserves more attention due to its valuable mechanical properties.